A Kitten Called Moonlight - Martin Waddell (London, United Kingdom Walker Books Ltd, 2006)
Written by an award-winning author and illustrator team. Charlotte's favourite story is about a little girl and her mummy who rescue a kitten from the sea. One moonlit night, the story comes true when she finds a little lost kitten by the sea, who she calls Moonlight. Charlotte loves her story even more because it's about her!
Keywords: Read Aloud -- Read Aloud